2021
DOI: 10.3389/fmats.2021.746022
|View full text |Cite
|
Sign up to set email alerts
|

Review of Self-sensing Capability of Ultra-high Performance Concrete

Abstract: Ultra-high performance concrete (UHPC) has the inherent potential to self-sensing capability due to its inclusion of steel fibers or other electrically conductive materials. Many studies have investigated the electrical and piezoresistive properties of UHPC. With the incorporation of micro steel fibers, carbon nanotubes, carbon nanofibrils, or nano graphite platelets, it opens up great potential to allow UHPC to effectively sense stress, strain, and crack damage. Therefore, the UHPC-based structures can achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Materials that serve several functions simultaneously are called 'multifunctional' materials [1]. Cement-based composites can provide self-healing [2][3][4][5][6], self-cleaning [7][8][9][10][11], electromagnetic wave shielding [12][13][14][15][16] and self-sensing [17][18][19][20][21] properties as well as being a structural element. The sensing technology electrically reveals the stresses on the structure and allows to comment on the state of live or dead loads on the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Materials that serve several functions simultaneously are called 'multifunctional' materials [1]. Cement-based composites can provide self-healing [2][3][4][5][6], self-cleaning [7][8][9][10][11], electromagnetic wave shielding [12][13][14][15][16] and self-sensing [17][18][19][20][21] properties as well as being a structural element. The sensing technology electrically reveals the stresses on the structure and allows to comment on the state of live or dead loads on the structure.…”
Section: Introductionmentioning
confidence: 99%
“…durability, which can effectively address the above issues and realize the real-time minoring [38][39][40][41]. In addition, it is worth noting that the conductive and self-sensing functions of SSUHPC are enhanced by the following key points: (1) The absence of coarse aggregates in the SSUHPC matrix allows for the favorable formation of conductive paths by the functional fillers [42].…”
Section: Introductionmentioning
confidence: 99%
“…Those engineering properties may prevent the initiation of microcrack formation in the cementitous matrix, even at very early ages [25]. Previous studies revealed that CNTs, namely MWCNTs, improved the mechanical behaviour and durability properties of cement-based composites [26][27][28][29][30][31][32][33][34][35][36][37]. However, most of those studies concern conventional cement-based paste or mortar; those conclusions cannot be directly drawn to advanced concrete material families such as HPC or UHPC.…”
Section: Introductionmentioning
confidence: 99%